2006
DOI: 10.1002/acp.1200
|View full text |Cite
|
Sign up to set email alerts
|

Police officers ability to detect deception in high stakes situations and in repeated lie detection tests

Abstract: Thirty-seven police officers, not identified in previous research as belonging to groups that are superior in lie detection, attempted to detect truths and lies told by suspects during their videotaped police interviews. In order to measure consistency in their ability, the officers each participated in four different tests, each of which was on a different day. They were asked to indicate their confidence in being able to distinguish between truths and lies prior to the first test and after completing all fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…DePaulo (a frequent co-author on Bond's recent publications) reported that when the stakes are low it is harder to tell who is lying (DePaulo, Lanier, & Davis, 1983). Others since us, who also studied lying when the incentives and punishment can be presumed to be very high, have also reported higher than typical accuracy in judging deception, consistent with our reasoning and prior findings (Vrij, Mann, Robbins, & Robinson, 2006).…”
supporting
confidence: 81%
“…DePaulo (a frequent co-author on Bond's recent publications) reported that when the stakes are low it is harder to tell who is lying (DePaulo, Lanier, & Davis, 1983). Others since us, who also studied lying when the incentives and punishment can be presumed to be very high, have also reported higher than typical accuracy in judging deception, consistent with our reasoning and prior findings (Vrij, Mann, Robbins, & Robinson, 2006).…”
supporting
confidence: 81%
“…The few studies that have investigated this have produced reasonably consistent results, which differ from metaanalytic findings of low stakes deception detection (Bond & DePaulo, 2006), and suggest that people may be able to detect deception with accuracy substantially above chance levels: in a series of studies using videos of police interviews with suspects as stimulus materials Mann, Vrij & Bull, 2004Vrij & Mann, 2001a;Vrij, Mann, Robbins & Robinson, 2006), police officers' credibility judgements were consistently accurate at rates well above chance levels, at 68%, 65%, 69%, 64% and 72% respectively. These relatively high accuracy rates are important, as previous studies, using low stakes stimulus materials, have suggested that police officers are no more accurate than laypersons at detecting deception (for example, DePaulo & Pfeifer, 1986;Ekman & O'Sullivan, 1991;Meissner & Kassin, 2002).…”
mentioning
confidence: 97%
“…participants observed honest and deceptive individuals. In the majority of previous research investigating deception in high stakes situations, a within subjects stimulus materials design has been used Mann et al, 2004Vrij & Mann, 2001a;Vrij et al, 2006). In these studies, honest and deceptive sections of communications by individuals guilty of committing various crimes are compared, and this within subjects method is limited as it negates the possibility of examining the individuals holistically; i.e.…”
Section: Accuracy In Detecting High Stakes Liesmentioning
confidence: 99%
“…The sample size of pharmacists limited the study with respect to statistical power, as the low sample size may have prevented some significant results, particularly with the use of the Bonferroni correction. However, other studies in the deception detection field have used similarly sized samples of experts (see Vrij et al, 2006;Vrij and Mann, 2001;Lakhani and Taylor, 2002). There was also the possibility of selection effects, whereby the most proactive and interested pharmacists took the time to complete the survey.…”
Section: Limitationsmentioning
confidence: 97%